2021
DOI: 10.1136/tobaccocontrol-2021-056717
|View full text |Cite
|
Sign up to set email alerts
|

Associations of tobacco retailer density and proximity with adult tobacco use behaviours and health outcomes: a meta-analysis

Abstract: ObjectiveWe sought to conduct a systematic review and meta-analysis of evidence to inform policies that reduce density and proximity of tobacco retailers.Data sourcesTen databases were searched on 16 October 2020: MEDLINE via PubMed, PsycINFO, Global Health, LILACS, Embase, ABI/Inform, CINAHL, Business Source Complete, Web of Science and Scopus, plus grey literature searches using Google and the RAND Publication Database.Study selectionIncluded studies used inferential statistics about adult participants to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 80 publications
(36 reference statements)
0
34
0
Order By: Relevance
“…Further findings of higher substance (e-cigarette, alcohol, marijuana) use among university students, who live off-campus, confirms the persistence of the ongoing problem in this subpopulation [48] . More analysis is needed to determine the proximity and density of these substances' vendors within the college town as these factors are likely to contribute to the issue [49] . This deeper analysis is necessary in order to re-evaluate the current local policies on point-of-sale marketing and distribution of these products.…”
Section: Discussionmentioning
confidence: 99%
“…Further findings of higher substance (e-cigarette, alcohol, marijuana) use among university students, who live off-campus, confirms the persistence of the ongoing problem in this subpopulation [48] . More analysis is needed to determine the proximity and density of these substances' vendors within the college town as these factors are likely to contribute to the issue [49] . This deeper analysis is necessary in order to re-evaluate the current local policies on point-of-sale marketing and distribution of these products.…”
Section: Discussionmentioning
confidence: 99%
“…A 2021 systematic review and meta-analysis of 37 international studies looking at the relationship of tobacco retailing density and proximity to smoking prevalence concluded: "Across studies, lower levels of tobacco retailer density and decreased proximity are associated with lower tobacco use" (Lee, Kong et al 2021).…”
Section: Restrictions On the Number And Location Of Tobacco Retailersmentioning
confidence: 99%
“…A meta-analysis of 11 studies from six countries (Australia, Canada, India, New Zealand, Scotland, USA) about youth tobacco use found that greater retailer density near homes was associated with higher odds of past-month cigarette smoking (OR=1.08, 95% CI 1.04 to 1.13) 8. In addition, a meta-analysis of 27 studies from six Organisation for Economic Co-operation and Development countries (Australia, Canada, Finland, New Zealand, UK, USA) about adult tobacco use indicated that reductions in tobacco retailer density and proximity were associated with an estimated 2.5% reduction (95% CI 1.95 to 3.02) in the relative risk of tobacco use 9. Importantly, many of the associations were evident even after controlling for various individual-level and area-level covariates 8 9…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-analysis of 27 studies from six Organisation for Economic Co-operation and Development countries (Australia, Canada, Finland, New Zealand, UK, USA) about adult tobacco use indicated that reductions in tobacco retailer density and proximity were associated with an estimated 2.5% reduction (95% CI 1.95 to 3.02) in the relative risk of tobacco use 9. Importantly, many of the associations were evident even after controlling for various individual-level and area-level covariates 8 9…”
Section: Introductionmentioning
confidence: 99%